Use of Crowdsourced Online Surveys to Study the Impact of Architectural and Design Choices on Wellbeing - Altaf, Basma; Bianchi, Eva; Douglas, Isabella P.; Douglas, Kyle; Byers, Brandon; Paredes, Pablo E.; Ardoin, Nicole M.; Markus, Hazel R.; Murnane, Elizabeth L.; Bencharit, Lucy Z.; Landay, James A.; Billington, Sarah L. (Frontiers in Sustainable Cities, 2022)
There has been growing interest among scholars regarding the role of the built environment on occupant wellbeing. Across five studies conducted online from January 2018 to July 2021, we investigate the impact of design interventions (materials, light, and decor representing diverse identities) on several constructs indicative of wellbeing (sense of belonging, self-efficacy, and environmental efficacy), using self-reported metrics. We hypothesize that natural materials, natural light and diverse representations lead to higher self-reported scores compared to artificial materials, no natural light and non-diverse representations. We find that, while our results vary across individual experiments, the synthesized effects of materials and light on all three dependent measures hold consistent across studies, supporting our hypothesized outcomes. We also examine the influence of seasonality, survey platform and design, and independent variables' dosage on survey results. We conclude with a discussion on the challenges associated with researching the psychological as well as behavioral impacts of design interventions in indoor spaces.